2003
DOI: 10.2307/3557067
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ubiquitous through the Unusual: Color Symbolism in Pueblo Black-on-White Pottery

Abstract: One of the common design characteristics on black-on-white pottery from the eleventh and twelfth centuries in the northern American Southwest is the use of thin, parallel lines (hachure) to fill the interior of bands, triangles, or other forms. This essay explores a proposal offered by Jerry Brody that hachure was a symbol for the color blue-green. Brody's proposal is examined by exploring colors and color patterns used to decorate nonceramic material from the Chaco Canyon region of northwestern New Mexico. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
(3 reference statements)
0
27
1
2
Order By: Relevance
“…Chacoans built a number of large ceremonial structures, or "great kivas," suggesting an increased focus on community-level ritual (15). Finally, this time period also marks the widespread adoption of Gallup and Chaco Black-onwhite style ceramics with their distinctive hachure designs that potentially signify the propagation of a Chacoan ideology throughout the San Juan Basin (17). Coupled with other sources of data, Guiterman et al's (1) findings reinforce the importance of better understanding Chaco's ties to the Chuskan region during the Classic Bonito phase, a period defined by Chaco's growing regional influence and increasing construction labor demands.…”
Section: Implications For Chacomentioning
confidence: 99%
“…Chacoans built a number of large ceremonial structures, or "great kivas," suggesting an increased focus on community-level ritual (15). Finally, this time period also marks the widespread adoption of Gallup and Chaco Black-onwhite style ceramics with their distinctive hachure designs that potentially signify the propagation of a Chacoan ideology throughout the San Juan Basin (17). Coupled with other sources of data, Guiterman et al's (1) findings reinforce the importance of better understanding Chaco's ties to the Chuskan region during the Classic Bonito phase, a period defined by Chaco's growing regional influence and increasing construction labor demands.…”
Section: Implications For Chacomentioning
confidence: 99%
“…Others involved the depiction of flowers, clouds, rainbows, and riverine insects (see Hays-Gilpin and Hill 2000), lyrical description (e.g., Hill 1992), and metaphor in dress (e.g., Roediger 1941:132). J. J. Brody suspected that hachure on Chacoan pottery— shu'k’ish-pa-tsí-nan in Zuni (Cushing 1886:488)—might have represented the color blue-green (Plog 2003:670). To test Brody's hypothesis, Plog (2003:673) first identified instances where Pueblo potters suggested that hachure was, in fact, conceptualized as a color (Bunzel 1929:35, 42).…”
mentioning
confidence: 99%
“…Whereas Bonito phase (AD 920–1130) Chacoan culture emphasized expansion, ostentation, and nonlocal interaction (e.g., Judge 1989; Kantner 1999; Lekson 1999, 2007; Reed 2004; Swentzell 2004:50), Classic period (AD 1000–1130) Mimbres society developed as a small-scale, insular network with little evident connection to what was going on in the north. Given these differences, the few things held in common stand out, including the early introduction of large masonry pueblos, interest in Mesoamerican materials, noteworthy turquoise consumption, and the early use of black hachure on white-slipped pottery (see Anyon and LeBlanc 1984:306–307; Brody 2004; Crown and Hurst 2009; Lekson 1992:116, 1999:52–53; Plog 2003).
Figure 1. Map of New Mexico, showing locations of Chaco Canyon and Mimbres River Valley.
…”
mentioning
confidence: 99%
See 2 more Smart Citations